Arachidonic acid downregulates acyl-CoA synthetase 4 expression by promoting its ubiquitination and proteasomal degradation[S] - Chin Fung Kelvin Kan; Amar Bahadur Singh; Diana M. Stafforini; Salman Azhar; Jingwen Liu (Journal of Lipid Research, 2014)
ACSL4 is a member of the long-chain acyl-CoA synthetase (ACSL) family with a marked preference for arachidonic acid (AA) as its substrate. Although an association between elevated levels of ACSL4 and hepatosteatosis has been reported, the function of ACSL4 in hepatic FA metabolism and the regulation of its functional expression in the liver remain poorly defined. Here we provide evidence that AA selectively downregulates ACSL4 protein expression in hepatic cells. AA treatment decreased the half-life of ACSL4 protein in HepG2 cells by approximately 4-fold (from 17.3 ± 1.8 h to 4.2 ± 0.4 h) without causing apoptosis. The inhibitory action of AA on ACSL4 protein stability could not be prevented by rosiglitazone or inhibitors that interfere with the cellular pathways involved in AA metabolism to biologically active compounds. In contrast, treatment of cells with inhibitors specific for the proteasomal degradation pathway largely prevented the AA-induced ACSL4 degradation. We further show that ACSL4 is intrinsically ubiquitinated and that AA treatment can enhance its ubiquitination. Collectively, our studies have identified a novel substrate-induced posttranslational regulatory mechanism by which AA downregulates ACSL4 protein expression in hepatic cells.